Quantitative proteomic analysis of amphotericin B resistance in Leishmania infantum - Brotherton, Marie-Christine (Elsevier, 2014)
Amphotericin B (AmB) in its liposomal form is now considered as either first- or second-line treatment against Leishmania infections in different part of the world. Few cases of AmB resistance have been reported and resistance mechanisms toward AmB are still poorly understood. This paper reports a large-scale comparative proteomic study in the context of AmB resistance. Quantitative proteomics using stable isotope labeling of amino acids in cell culture (SILAC) was used to better characterize cytoplasmic and membrane-enriched (ME) proteomes of the in vitro generated Leishmania infantum AmB resistant mutant AmB1000.1. In total, 97 individual proteins were found as differentially expressed between the mutant and its parental sensitive strain (WT). More than half of these proteins were either metabolic enzymes or involved in transcription or translation processes. Key energetic pathways such as glycolysis and TCA cycle were up-regulated in the mutant. Interestingly, many proteins involved in reactive oxygen species (ROS) scavenging and heat-shock proteins were also up-regulated in the resistant mutant. This work provides a basis for further investigations to understand the roles of proteins differentially expressed in relation with AmB resistance.